Photoactivity, conversion kinetics, nanoreinforcement, post-curing, and electric/dielectric properties of functional 3D printable photopolymer resin filled with bare and alumina-doped ZnO nanoparticles. (December 2022) - Korčušková, Martina; Sevriugina, Veronika; Ondreáš, František; Svatík, Juraj; Tomal, Wiktoria; Vishakha, Vishakha; Ortyl, Joanna; Lepcio, Petr
Abstract: The addition of nanoparticles (NPs) into a polymer matrix represents a simple yet efficient tool for introducing or enhancing functional properties. 3D printing is a processing technique with unprecedented control over the micro- and macroscopic structure. Their combination creates a versatile fabrication tool for both professional and hobby users. However, some less intuitive effects brought about by NPs must also be considered. This study has thoroughly investigated the addition of bare and alumina-doped zinc oxide NPs into a representative free-radical photo-polymerization resin. The alumina doping suppressed the characteristic surface plasmon resonance of ZnO NPs. This absorption band was found crucial for the NP photoactivity and, subsequently, the conversion kinetics, post-curing, thermomechanical, and electric/dielectric properties of the nano-filled resins. Furthermore, three experimental techniques for assessing the photocuring kinetics – real-time FTIR, photo-DSC, and Jacobs working curves, were compared and resolved. Each yielded a completely different conclusion due to the photothermal effect and nanoreinforcement. The presented data shall aid with designing and testing of functional photopolymer nanocomposites for 3D printing and other low-intensity curing applications. Highlights: Functional nanocomposite photo-curable 3D printing resins. Effect of alumina doping on the ZnO nanoparticles photo-activity. Photothermal and nanoreinforcement effect. Inconsistency of curing assessment techniques (FTIR, DSC, Jacobs working curve). Thermomechanical and electric/dielectric properties of nanocomposite resins.